Examining the Effect of Parent’s Supports Toward the Champion Motivation Possessed by Athletes Samarinda in 2018 - Nanda Alfian Mahardhika; Yulia Tri Kusumawati; Jeane Betty Kurnia Jusuf; Januar Abdilah Santoso; Andri Tria Raharja; Julianur Julianur (Universitas Muhammadiyah Kalimantan Timur, 2019)
The aim of this research is to examine the effect of parent’s supports toward the champion motivation possessed by athletes in Samarinda city. This research method used in this research is descriptive qualitative method. The instrument of research is the questionnaires shared to 50 parent’s Silat athletes in Samarinda. The population of this research is all parents athletes and Silat athletes in Samarinda. The saturated sample research technique is used to the all over population as the sample and it presented in the percentage term. This research is expected to be done in 6 month periods. The result of this research is that the support parent’s athletes gained a positive trend with 93.4% and the champion motivation of athlete also had the same pattern with 97.2%.